Federal Practitioner 2023
DOI: 10.12788/fp.0357
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Related Adverse Events Associated With PCSK9 Inhibitors in a Veteran Population

Abstract: Background: Statins and PCSK9 inhibitors (PCSK9i) are used to lower low-density lipoprotein cholesterol and reduce cardiovascular events, yet some patients are unable to tolerate statin therapy due to muscle-related adverse events (AEs). The effect of PCSK9i on muscle-related AEs is not well studied, and available data show inconsistent incidence rates. Methods: The primary study outcome was to determine the percentage of patients who developed muscle-related PCSK9i AEs. A secondary outcome was to analyze data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Unfortunateley, this hypothesis does not seem valid for muscle disorders induced by PCSK9 inhibitors or ezetimibe, since they do not deplete ubiquinone. Furthermore, it has been observed that muscle disorders induced by PCSK9 inhibitors are evident later in the treatment, with respect to statins [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunateley, this hypothesis does not seem valid for muscle disorders induced by PCSK9 inhibitors or ezetimibe, since they do not deplete ubiquinone. Furthermore, it has been observed that muscle disorders induced by PCSK9 inhibitors are evident later in the treatment, with respect to statins [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective cohort study comprised of 137 participants reported that 24 patients (17.5%) developed muscle-related adverse reactions such as myalgia, myopathies, etc. [ 35 ]. The most commonly used PCSK9 inhibitors, evolocumab and alirocumab, were found to be associated with musculoskeletal and connective tissue disorders (including back pain, myalgia, pain in extremity, arthralgia, muscle spasms), in a recent retrospective study based on the Food and Drug Administration adverse event reporting system database [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…5. Therapeutic effect is severely attenuated due to the development of antibodies 14,15 Tables 6, 7 and 8…”
Section: Advantages Of Pcsk 9 Inhibitorstablementioning
confidence: 99%